Exploring strategy-making in "non-new public management" public services settings: The case of European Union agencies - Edoardo Ongaro; Ewan Ferlie (Administrative Sciences, 2019)
A growing public management literature has debated whether strategic management models originally developed for private firms are also relevant to contemporary public agencies. Thus far, it has been easier to apply strategic management models centred on competitive advantage in jurisdictions in which new public management (NPM) reforms have left an enduring inheritance, with the emphasis in these settings on the autonomization of public agencies and a prominent concern with "performance". Based on the case study of public agencies in the European Union, we argue there is potential to apply strategic management models in other jurisdictions where the penetration of NPM has been much lower, provided certain conditions of agency autonomy are met and factors-such as stakeholders' expectations stimulating the adoption of strategic management models-perform as the functional equivalent of the pressures provided by NPM incentivization systems. The paper contributes to the literature aimed at employing the discipline of strategic management-a thriving field of inquiry business administration and management-as a valuable source of knowledge for the advancement of public management.
Keywords: 350; public management; public strategic management; European Union; public agencies; research policy; educational and vocational training policy